2013
DOI: 10.2196/jmir.2852
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Social Media in Online Weight Management: Systematic Review

Abstract: BackgroundSocial media applications are promising adjuncts to online weight management interventions through facilitating education, engagement, and peer support. However, the precise impact of social media on weight management is unclear.ObjectiveThe objective of this study was to systematically describe the use and impact of social media in online weight management interventions.MethodsPubMed, PsycINFO, EMBASE, Web of Science, and Scopus were searched for English-language studies published through March 25, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
119
0
8

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 129 publications
(127 citation statements)
references
References 40 publications
0
119
0
8
Order By: Relevance
“…89 Another untapped area similarly lies in social media, for its peer support outlets. 90 We found it remarkable that few (2/16, 13 %) studies presented open-source or non-proprietary interventions. 63,73 Most websites and tools studied in trials are entirely unavailable to the practicing PCP, even though many patients could conceivably benefit from access.…”
Section: Areas For Future Researchmentioning
confidence: 90%
“…89 Another untapped area similarly lies in social media, for its peer support outlets. 90 We found it remarkable that few (2/16, 13 %) studies presented open-source or non-proprietary interventions. 63,73 Most websites and tools studied in trials are entirely unavailable to the practicing PCP, even though many patients could conceivably benefit from access.…”
Section: Areas For Future Researchmentioning
confidence: 90%
“…A recent systematic review of weight management interventions targeting women aged 18-35 years concluded that Bhigh-quality randomized controlled trials evaluating interventions that are tailored to the unique needs of young women, and that can be disseminated broadly, are urgently needed to address the unmet needs of this high-risk group.^ [33] One possible approach to addressing this critical research need is by reaching and intervening on obesity among women of childbearing age via Twitter. Online social networking in general is a novel, understudied weight loss tool [18], with great potential for impacting the obesity epidemic. Two recent systematic reviews indicated that online social networks have been primarily used as an adjunct to in-person or web-based weight loss interventions, rather than as the primary treatment modality [18,19].…”
Section: Discussionmentioning
confidence: 99%
“…Online social networking in general is a novel, understudied weight loss tool [18], with great potential for impacting the obesity epidemic. Two recent systematic reviews indicated that online social networks have been primarily used as an adjunct to in-person or web-based weight loss interventions, rather than as the primary treatment modality [18,19]. We recently conducted a series of pilot studies that demonstrated that delivering a weight loss intervention via a private Twitter group is feasible and acceptable [34].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, social media has been mostly used in combination with other delivery modalities (e.g. in-person groups, text messages) [6,[32][33][34], and few studies have evaluated the feasibility and effectiveness of delivering a weight loss intervention solely via a publicly available social media network (e.g. Twitter, Facebook) [23,25].…”
Section: Introductionmentioning
confidence: 99%